Kompas’ Discourse on Literacy and Numeracy: From Stagnation to Collaboration - Fafi Inayatillah; Abdul Muhaiminul Aziz (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
Students’ literacy and numeracy competencies are important issues in Indonesian education policy. In April 2026, the Ministry of Primary and Secondary Education (Kemendikdasmen) issued a new policy to address this issue, as reported by Kompas.com. This news provides a representative overview of the policy changes and is rich in discursive elements that are of interest for critical discourse analysis. This article aims to analyze how the policy discourse on strengthening literacy and numeracy is constructed in the news text “Government Acknowledges Literacy and Numeracy Levels Remain Low (Pemerintah Akui Tingkat Literasi dan Numerasi Masih Rendah)” (Kompas, 9 April 2026). This study employs Norman Fairclough’s three-dimensional critical discourse analysis: text, discourse practices, and sociocultural practices. The results show that the text systematically constructs a reality of crisis through the metaphor of “homework (pekerjaan rumah)”, the objectification of PISA data, the repetition of the word “collaboration”, and direct quotations from official actors. On the other hand, this discourse presents multi-stakeholder collaboration as the sole solution. This legitimatizes the shift of educational responsibility from the state to private and foreign entities. Furthermore, this discourse closes the space for criticism and policy alternatives that are more oriented towards social justice through the exclusion of grassroots voices, the erasure of structural causes, a closed narrative structure, the reproduction of neoliberal ideology, the dominance of PISA data, and the obscuring of state responsibility. This points to the presence of a neoliberal ideology behind this discourse, as well as the reduction of education to an investment framework. This finding encourages readers to view narratives surrounding ‘multi-stakeholder collaboration’ more critically.